Application of wood structures for the analysis of the electrical chain in a sinusoidal and periodical non-sinusoidal mode of work - Simeonova, Tsvetelina; Velkov, Alex (Yearbook Telecommunications, 2018)
The purpose of the study is to develop a methodology using tree structures in single-source linear circuit analysis in sinusoidal and periodic non-sinusoidal mode. The relationship between parameters of elements and parameters of equivalent elements and their corresponding electrical magnitude, current and voltage, with a specified source influence by analysis of the electric circuit with a tree description of the equivalent transformations is used. The following results were obtained: - Equivalent tree structure of the electrical circuit for determining the equivalent complex resistance (in the rights direction) as well as for determining the complex magnitudes (in the opposite direction). - An algorithm for determining the equivalent complex resistance, as well as an algorithm for determining complex values based on equivalent transformations. The work has received the following contributions: - A methodology is proposed for the analysis of a linear electric circuit with a single source in a sinusoidal and periodic non-sinusoidal regime based on a tree structure. - It is suggested that the training of students in the area of theoretical electrical engineering include the analysis of the electric circuit in sinusoidal and periodic non-sinusoidal mode, according to the proposed algorithm for application of tree structures including an equivalent tree scheme and demo calculations on it.